(3HhGQb GdEdeGY aj JcajQ ef jMQe GdSeGYs - (3CMeO Hf eMeO Hf eMeO Hf CMeO, CHh GdaJhM, eLO GdOjf GdWhSj GdZRGdj,J (B520 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd YHjO Gddg CMeO Hf eMeO GdWhSi GdZRGdi QMeI Gddg Ydjg SCdJ ENhGfi Cgd GdehGLjO KHJg Gddg JYGdi Ydi efGgL GdESJbGeI Yf MbjbI GdSeGY haGFOJg s
(3BNQgG (B:s
(3EPG de jQO HJMQje GdSeGY fU ef cJGH Gddg JYGdi hdG SfI QShdg Udi Gddg Ydjg hSde cedJ HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B214 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B147s
(3GdagQSJ EHf GdfOje(B: (3L (B1 - (3U (B197s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs